2023
DOI: 10.3390/prosthesis5030055
|View full text |Cite
|
Sign up to set email alerts
|

Fretting Wear and Corrosion-Related Risk Factors in Total Hip Replacement: A Literature Review on Implant Retrieval Studies and National Joint Replacement Registry Reports

Khashayar Ghadirinejad,
Christopher W. Day,
Roohollah Milimonfared
et al.

Abstract: Fretting corrosion is a known failure mechanism of total hip replacement (THR) that can lead to revision surgery. Implant retrieval studies have thoroughly documented the occurrence of fretting corrosion in THR implants and its correlation with implant- and patient-related factors. Although implant retrieval studies benefit both clinicians and implant manufacturers, the limitations of these types of studies need to be acknowledged. For example, while some factors are routinely investigated for a possible corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 134 publications
1
2
0
Order By: Relevance
“…The reason might be due to the enhanced stability of calcium ion binding to the surface of chitosan nanoparticles. Similar results were also observed in the study by Archana et al [70].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reason might be due to the enhanced stability of calcium ion binding to the surface of chitosan nanoparticles. Similar results were also observed in the study by Archana et al [70].…”
Section: Discussionsupporting
confidence: 92%
“…Savita et al reported that both agents showed the highest bacterial reduction against E. faecalis in case of persistent infections [69]. Literature evidence has also shown that 2% CHX to be more efficient in bacterial reduction than 2% chitosan [70]. The reason might be due to the increased diffusion of CHX into the dentinal tubules [48,71,72].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of HRT on implant osseointegration specifically have not been extensively studied. Previous investigations examining the relationship between HRT and implant outcomes have yielded conflicting results ( Chhikara et al, 2023 , Ghadirinejad et al, 2023 , Soegiantho et al, 2023 , Wellington et al, 2023 ). Some studies suggest a detrimental impact of HRT on implant osseointegration, while others report no significant association ( Giro et al, 2007 , Giro et al, 2008 , Seratiuk Flores et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%